Evaluation of mupirocin ointment in control of central venous catheter related infections: a randomized clinical trial - Rezaei J (Tehran University Medical Journal, 2009)
"n Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 st1":*{behavior:url(#ieooui) } /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Arial; mso-bidi-theme-font:minor-bidi;} Background: Central venous catheter (CVC) related infections are important complications of cathter application. This study assessed the usefulness of mupirocin in prevention and control of these infections."n"nMethods: In this randomized clinical trial, consecutive surgical patients requiring central venous catheter (for more than 2 days) in Amir-Alam Hospital from 2006-2008 were enrolled. Patients were divided in two groups; in "case group" patients received topical mupirocin 2% every 48 hours at the time of insertion of catheter and dressing change and for "control group" mupirocin was not used. All of the patients received chlorhexidine and enoxoparin as complementary treatments. Two groups were comparable in regard of age, sex and risk factors."n"nResults: One hundred eighteen patients enrolled in the study (57 in case and 61 in control group) completed the study. 84 catheters in case group and 88 catheters in control group were inserted. The catheters in 90% of patients were inserted in jugular vein. At the end of study 29(16.8%) patients (16 in control versus 13 in case group) had catheter colonization (p=NS). Catheter related bloodstream infection was observed in 16(9.3%) patients (6 in case versus 10 in control group) (p=NS).Catheter related local infection was seen in 2(1.1%) patients of control versus none of mupirocin group. (p=NS)."n"nConclusions: Mupirocin was not effective to control and prevention of bacterial colonization and catheter related infection